1996
DOI: 10.1053/jhep.1996.v24.pm0008781327
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of p16INK4 in hepatocellular carcinoma

Abstract: dispose the hepatocytes to uncontrolled growth and maligWe analyzed the p16 INK4 status of 6 hepatocellular carnant transformation as a result of disruption of the cell cycle's cinoma (HCC) cell lines and 32 primary HCC tumors, regulatory system. Mammalian cell-cycle progression is reguincluding 9 early-stage tumors, to determine whether lated by the sequential activation and inactivation of various p16 INK4 tumor-suppressor gene inactivation participates cyclin-dependent kinases (cdk) at different stages of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 5 publications
(9 reference statements)
7
26
3
Order By: Relevance
“…However, as shown in Figure 2b, p16 protein expression was undetectable in cell lines STA-ET-3, the STA-ET-7 series, and STA-ET-8 expressing a p16 transcript (compare to Figure 2a and 3b). These results indicate that, in addition to homozygous gene loss, p16 is frequently inactivated by post-transcriptional mechanisms in Ewing tumors as has been previously observed in hepatocellular carcinoma (Hui et al, 1996).…”
Section: Status and Expression Of P15/p16 Genessupporting
confidence: 82%
“…However, as shown in Figure 2b, p16 protein expression was undetectable in cell lines STA-ET-3, the STA-ET-7 series, and STA-ET-8 expressing a p16 transcript (compare to Figure 2a and 3b). These results indicate that, in addition to homozygous gene loss, p16 is frequently inactivated by post-transcriptional mechanisms in Ewing tumors as has been previously observed in hepatocellular carcinoma (Hui et al, 1996).…”
Section: Status and Expression Of P15/p16 Genessupporting
confidence: 82%
“…Recently, the locus of a tumor suppressor gene, p16 INK4 , coding for an inhibitor of cyclin D1/Cdk4, was found to be frequently lost in various malignancies. 35 Inactivation of the p16 INK4 gene has been reported in various human cancers, including human HCC, and in half of HCC cell lines and 34% of HCC tissues, p16 INK4 protein is not detected by immunoblot, 36 suggesting that the level of p16 INK4 is down-regulated. In addition, Ray et al 37 reported that the HCV core protein appears to act as a promoter of cell growth by repressing the transcription of another Cdk inhibitor (CKI), p21 WAF1 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that there might be another mechanism inactivating p16 and p15 genes in human primary hepatocarcinoma [5][6][7][8][9] . It has been demonstrated that aberrant methylation of CpG islands, which are CpG dinucleotide rich region located mainly in the promoter regions of many gene, serves as an alternative mechanism for inactivation of the tumor suppressor gene in cancers [10] .…”
Section: Introductionmentioning
confidence: 99%